ANALISA PERENCANAAN RUNWAY 10 TAHUN KEDEPAN DI BANDARA NGLORAM KABUPATEN BLORA JAWA TENGAH - Alfia Nur Rahmawati (DEARSIP : Journal of Architecture and Civil, 2023)
Abstract Ngloram Airport – Blora is an airport located 40 km from the center of Blora city which is managed by the Ministry of Transportation after being donated by the Ministry of Energy and Mineral Resources. At the time of writing, Ngloram – Blora Airport still has the status of a Service Unit under the Airport Management Unit. The existing condition of this airport is that it has a runway with dimensions of 1500 m x 30 m and the most critical aircraft is the ATR 72-600. It is stated in KM 231 of 2019 concerning Determining the Location of Ngloram Airport that the critical aircraft listed in the phase III development plan are new, larger critical aircraft that are planned for operation. Given this, in order for this type of aircraft to operate optimally, it requires extending and widening the runway. The aim of this research is to determine the actual need for runway length in accordance with the Airplane Reference Field Length (ARFL) and runway width in accordance with the type of aircraft planned to operate, and also to know the sufficient thickness of pavement along with the budget ceiling required for the work. -the job in question. Based on the results of the analysis that has been carried out, the dimensions of the extension are 1000 meters with a width of 45 meters and the widening of the existing runway is 15 meters with a total pavement thickness of 82.5 cm. With the thick pavement construction as stated, a PCN value of 50 F/C/X/T was obtained from the calculation of the FAARFIELD 1.42 software application and the budget ceiling required for these works was Rp. 73,663,700,000.00 Keywords: Runway, runway l Abstract Ngloram Airport – Blora is an airport located 40 km from the center of Blora city which is managed by the Ministry of Transportation after being donated by the Ministry of Energy and Mineral Resources. At the time of writing, Ngloram – Blora Airport still has the status of a Service Unit under the Airport Management Unit. The existing condition of this airport is that it has a runway with dimensions of 1500 m x 30 m and the most critical aircraft is the ATR 72-600. It is stated in KM 231 of 2019 concerning Determining the Location of Ngloram Airport that the critical aircraft listed in the phase III development plan are new, larger critical aircraft that are planned for operation. Given this, in order for this type of aircraft to operate optimally, it requires extending and widening the runway. The aim of this research is to determine the actual need for runway length in accordance with the Airplane Reference Field Length (ARFL) and runway width in accordance with the type of aircraft planned to operate, and also to know the sufficient thickness of pavement along with the budget ceiling required for the work. -the job in question. Based on the results of the analysis that has been carried out, the dimensions of the extension are 1000 meters with a width of 45 meters and the widening of the existing runway is 15 meters with a total pavement thickness of 82.5 cm. With the thick pavement construction as stated, a PCN value of 50 F/C/X/T was obtained from the calculation of the FAARFIELD 1.42 software application and the budget ceiling required for these works was Rp. 73,663,700,000.00 Keywords: Runway, runway length and width, own estimated price, FAARFIELD 1.42.